An NHC‐Stabilised Phosphinidene for Catalytic Formylation: A DFT‐Guided Approach. Issue 45 (25th June 2021) - Sreejyothi, P.; Bhattacharyya, Kalishankar; Kumar, Shiv; Kumar Hota, Pradip; Datta, Ayan; Mandal, Swadhin K.
Abstract: In recent years, the applications of low‐valent main group compounds have gained momentum in the field of catalysis. Owing to the accessibility of two lone pairs of electrons, NHC‐stabilised phosphinidenes have been found to be excellent Lewis bases; however, they cannot yet be used as catalysts. Herein, an NHC‐stabilised phosphinidene, 1, 3‐dimethyl‐2‐(phenylphosphanylidene)‐2, 3‐dihydro‐1 H imidazole (1), for the activation of CO2 is reported.A closer inspection of the CO2 activation process by DFT calculations along with intrinsic bond orbital analysis shows that phosphinidene is associated with phenylsilane through a noncovalent π‐π interaction between two phenyl rings which activates the Si−H bond facilitating hydride transfer to the CO2 molecule. Detailed DFT studies along with spectroscopic experiments were combined to understand the mechanism of CO2 activation and its catalytic reductive functionalisation leading to the formylation of a range of chemically inert primary amides under mild reaction conditions. Abstract : Introducing a low‐valent phosphorus compound to the arena of catalysis : A N‐heterocyclic carbene‐stabilised phosphinidene (1 ) was used for the activation of CO2 . DFT calculations showed that the nucleophilicity of the phosphorus centre and a noncovalent π‐π interaction between the phenyl rings of phenylsilane and the catalyst synergistically drive the formylation of primary amides by CO2 under mild conditions.